2017
DOI: 10.1002/term.2410
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensation across borders: fibroblasts inside a macroporous scaffold sense and respond to the mechanical environment beyond the scaffold walls

Abstract: In tissue defects, cells face distinct mechanical boundary conditions, but how this influences early stages of tissue regeneration remains largely unknown. Biomaterials are used to fill defects but also to provide specific mechanical or geometrical signals. However, they might at the same time shield mechanical information from surrounding tissues that is relevant for tissue functionalisation. This study investigated how fibroblasts in a soft macroporous biomaterial scaffold respond to distinct mechanical envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…[11,19,22,31,32] In agreement with this, we observed a timedependent scaffold contraction, both in axial and radial direction, under supplementation of ascorbic acid that is required for collagen fibrillogenesis (Figure 2a). [11,19,22,31,32] In agreement with this, we observed a timedependent scaffold contraction, both in axial and radial direction, under supplementation of ascorbic acid that is required for collagen fibrillogenesis (Figure 2a).…”
Section: In Vitro Tissue Contraction Depends On the Presence Of Collasupporting
confidence: 77%
See 4 more Smart Citations
“…[11,19,22,31,32] In agreement with this, we observed a timedependent scaffold contraction, both in axial and radial direction, under supplementation of ascorbic acid that is required for collagen fibrillogenesis (Figure 2a). [11,19,22,31,32] In agreement with this, we observed a timedependent scaffold contraction, both in axial and radial direction, under supplementation of ascorbic acid that is required for collagen fibrillogenesis (Figure 2a).…”
Section: In Vitro Tissue Contraction Depends On the Presence Of Collasupporting
confidence: 77%
“…Only individual collagen fibrils were identified after 3 d of culture but over time, a dense network of fibrillar collagen formed that followed the structural alignment of cells and fibronectin fibers along the scaffold pores (Figure 1e-g). [11,30] Taken together, we observed a time-dependent cellular selforganization and a consecutive deposition of fibronectin and fibrillar collagen within the channel-like scaffold pores resulting in a dense, highly aligned ECM network with almost identical structural properties as the cell-network. The limited contact to the scaffold material and the long-range organization indicated that the tissue formed inside the scaffold pores collectively organized on a macroscopic scale.…”
Section: Synthetic Biomaterials Niche As Model For Wound Healingmentioning
confidence: 67%
See 3 more Smart Citations